Poor sleep quality, employment status, and female gender as risk factors for overweight and obesity among Malaysian adults - Mohmad Hasim, Muhamad Hishamudin; Gunalan, Amarlashri; Lim, Christopher Thiam Seong; Lim, Yin Sze; Cheng, Shi Hui (Korean Society of Sleep Medicine, 2025)
Background and Objective The increasing prevalence of overweight and obesity among Malaysian adults necessitates a study to identify contributing factors. This study aims to determine the prevalence of overweight and obesity among Malaysian adults and identify associated sociodemographic and lifestyle factors. Methods A cross-sectional study involving 308 Malaysian adults aged 18 to 67 years was conducted via online platforms. Data were collected using the Pittsburgh Sleep Quality Index, along with sociodemographic information and self-reported body mass index. All statistical analysis was performed using SPSS version 28. Results The prevalence of overweight among the participants was 38%, while 26.9% were classified as obese. Full-time employment status (adjusted odds ratio [aOR], 2.308; 95% confidence interval [CI], 1.035–3.760; p=0.004) and poor sleep quality (aOR, 1.839; 95% CI, 1.078– 3.138; p=0.025) were significantly associated with an increased risk of being overweight or obese. Conversely, men were found to have lower odds of being overweight or obese (aOR, 0.383; 95% CI, 0.215–0.684; p<0.001). Conclusions The study highlights the alarming prevalence of overweight and obesity among Malaysian adults. Factors associated with an increased risk of these conditions include full-time employment status, poor sleep quality, and female gender. These findings emphasize the need for targeted interventions tailored to specific at-risk groups, such as full-time employees and women, as well as those experiencing poor sleep quality. Interventions to promote healthy sleeping practices should also be taken into consideration to address the growing prevalence of overweight and obesity.